Managing successful projects with PRINCE2 - Great Britain. Office of Government Commerce; Great Britain. Office of Government Commerce. &#x000A (London : TSO, 2009)
Presents a project management method - the principles, processes and techniques that enable individuals and organisations to successfully deliver their projects within time, cost and quality constraints. This handbook explains the principles that underpin PRINCE2. It describes the PRINCE2 processes in their entirety.
"OGC official product"--Cover.
Includes bibliographical references and index.
Keywords: Project management -- Computer programs; Management information systems; PRINCE2 (Computer file) Industry -- methods. Project management -- Methodology. &#x000A